An experimental investigation on the effect of use of nanofluids in radiant floor heating systems - Karakoyun, Yakup; Acikgoz, Ozgen; Kucukyildirim, Bedri Onur; Yumurtaci, Zehra; Dalkilic, Ahmet Selim (ELSEVIER SCIENCE SA, 2021)
Hydronic radiant heating systems are widely being run particularly in association with low temperature heat sources. These thermal units are capable of providing high energy saving potential as well as improvement in thermal comfort. Thus, focus on such systems have considerably ascended recently. In this context, augmentation methods have been employed to enhance heat transfer performance of many thermal systems. The use of ultrafine particles in the fluids is considered to be one of the passive techniques, and hence physical properties have been improved compared to the base fluid. Currently, four working fluids' inlet temperatures are varied from 30 degrees C to 60 degrees C, while the mass flow rates are 0.056 and 0.09 kg/s for the heating from floor, and heating from floor along with cooling from walls. Consequently, the examined nanofluids having multi wall carbon nanotube (0.7% vol. cont.) and aluminium oxide (1.26% vol. cont.) have demonstrated better heat transfer performance compared to pure water for similar operating conditions. Nanofluids of greater concentrations such as (0.7% vol. cont.) and (1.26% vol. cont.) have resulted in improvements within the range of 1.7% and 4.9%. Given the improvement in heat transfer acquired, a promising evaluation can be inferred with respect to nanofluids being operated as working fluids in such systems. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Nanofluids; CNT; Al2O3; Radiant floor heating; Thermal output; OPTIMIZATION; PERFORMANCE; DENSITY; WATER; Construction & Building Technology; Energy & Fuels; Engineering